The vitamin D positive feedback hypothesis of inflammatory bowel diseases. (June 2019) - Linneman, Z.; Reis, C.; Balaji, K.; Moore, J.; Braude, S.
Abstract: While it appears that there are a variety of factors that exacerbate IBD, it is frustrating that symptoms can persist and worsen even when environmental insults are removed. We suggest that there may be a positive feedback loop which perpetuates the inflammatory response in IBD patients. The loop is triggered by vitamin D deficiency which reduces calcium uptake. Lowered vitamin D and calcium interfere with anti-inflammatory pathways. Inflammation of the mucosa inhibits absorption of calcium and thus perpetuates the reduced anti-inflammatory response. A number of predictions follow from this hypothesis and are supported by geographic and lifestyle patterns in IBD incidence and prevalence.